Culture: An Empirical Investigation of Beliefs, Work, and Fertility. A Verification and Reproduction of Fernández and Fogli (American Economic Journal: Macroeconomics, 2009) - Victor Gay (Journal of Comments and Replications in Economics (JCRE), 2023)
In this article, I perform a verification and a reproduction of the main results in Fernández and Fogli (2009), which estimates the role of culture in explaining the labor and fertility decisions of second generation immigrant women to the United States in 1970. While I am able to verify Fernández and Fogli's (2009) main results as well as their robustness relative to both labor and fertility decisions, I am unable to reproduce them relative to labor decisions in alternative samples drawn from the same underlying population.
https://doi.org/10.15456/j1.2022252.0530923662
Keywords: J13; J16; J22; J24; Z13; 330; Culture; Female Labor Force Participation; Fertility; Replication